Release of Perfluoroalkyl Substances From Melting Glacier of the Tibetan Plateau: Insights Into the Impact of Global Warming on the Cycling of Emerging Pollutants. Issue 13 (8th July 2019) - Chen, Mengke; Wang, Chuanfei; Wang, Xiaoping; Fu, Jianjie; Gong, Ping; Yan, Juping; Yu, Zhengliang; Yan, Fangping; Nawab, Javed
Abstract: The Tibetan Plateau (TP) has encountered rapid warming, with more than 50% of lakes expanding and 80% of glaciers retreating. Melting glaciers are known as a secondary source of pollutants, but the dynamics and release features of water‐soluble emerging chemicals have not been studied in the TP. Glacial ice and snow, meltwater runoff, rain, and lake water were collected in Nam Co basin, in the central TP. The total concentrations of perfluoroalkyl acids (PFAAs) were 1, 413 pg/L for glacial ice, followed by 1, 277 pg/L for meltwater runoff, 980 pg/L for lake water, and 616 pg/L for rain. Perfluorobutanoic acid is dominant in runoff and glacial ice, while lake water contained high proportions of perfluorobutane sulfonate and perfluorooctane sulfonate. During the melting season, meltwater runoff generally had greater PFAAs concentrations, and the PFAAs release fluxes were strongly related to the glacial melt intensity. Due to the direct input of PFAAs by melted glaciers, south shore of Lake Nam Co contained higher PFAAs concentrations. The estimated input fluxes of PFAAs to the lake by rain and glacial and nonglacial runoff were 1, 425, 1, 342, and 2, 192 mg/day, respectively. Taken together, these evidences suggest that melting glaciers are sources of PFAAs, while the lake is the receptor. Given the continuity of glacial melt and high concentrations of water‐soluble emerging pollutants in glacier, the melting process will increase the risks of emerging pollutants to freshwater sources and should be of great concern. Key Points: The PFASs released by glaciers have become a secondary source of PFASs in Lake Nam Co in the central Tibetan Plateau PFAA transport dynamics in glacial runoff is related to the chain length of PFAAs and the melting process of ice and snow Precipitation and glacial and nonglacial runoffs contribute 27.1%, 28.7%, and 44.2% of the total annual PFAAs input in Lake Nam Co, respectively